Just Solidarity: The Key to Fair Health Care Rationing (Diametros, 2015)
I agree with Professor ter Meulen that there is no need to make a forced choice between “justice” and “solidarity” when it comes to determining what should count as fair access to needed health care.  But he also asserts that solidarity is more fundamental than justice.  That claim needs critical assessment. Ter Meulen recognizes that the concept of solidarity has been criticized for being excessively vague.  He addresses this criticism by introducing the more precise notion of “humanitarian solidarity.”  However, I argue that these notions are still not precise enough and are in need of behavioral translation, especially in relation to the problem of fair health care rationing.  More specifically, I argue that translation ought to take the form of a well-ordered process of rational democratic deliberation, which I describe and defend in this essay.  Such a process is what is required to construct a working model of just solidarity as opposed to a merely abstract idealization of just solidarity.